combining ability for yield and yield contributing characters of white jute (Corchorus capsularis L.) - Khatun, Rahima; Sarker, RH; Sobhan, MA (Bangladesh Journal of Botany, 2010)
Crosses were made between three varieties and seven accessions of white jute (Corchorus capsularis L.) in all possible combinations to establish 10 × 10 full diallel set. Variances for general combining ability (GCA) and specific combining ability (SCA) were significant or highly significant for all the characters indicating additive and non-additive gene actions played predominant role for expression of these characters. The magnitudes of GCA variance were higher than the corresponding SCA variance confirmed the predominance of additive genetic variations for these traits. The variety CVL-1 and Acc. 1831 were good general combiners for plant height, technical height, base diameter, number of nodes, bark weight, fibre weight and stick weight. Crosses, var. CVL-1 × Acc. 1831, Accs. 3695 × 4087, Accs. 1831 × 1833, Accs.1831 × var.CC-45, Acc. 2146 × var. A-38 and Acc. 2146 × var.CC-45 revealed significant positive SCA effect for fibre weight. Significant reciprocal SCA effect was observed in crosses, Accs.1832 × 3695, Accs.1833 × 1831 and Acc. 4087 × var.CVL-1. Crosses, var. CVL-1 × Acc.1831, Accs. 3695 × 4087, Acc.1831 × var.CC-45, Acc.2146 × var.CC-45 and a reciprocal cross, Accs.1833 × 1831 were found to be good specific combiners for bark weight, fibre weight and stick weight. Key words: Combining ability; Fibre yield; White jute DOI: 10.3329/bjb.v39i1.5530 Bangladesh J. Bot. 39(1): 79-85, 2010 (June)